Using the Theoretical Framework of Acceptability in Assessing Chronic Disease Management Programs - Adila Solida; Arnild Augina Mekarisce; Evy Wisudariani (Lembaga Pengembangan Kinerja Dosen, 2023)
The problem of the increasing incidence of chronic diseases in Indonesia has encouraged the development of the Chronic Disease Management Program. However, in Jambi City, the implementation of various Prolanis initiatives has not been optimal, and community participation in the program is still low. The aim of this research is to describe the public's assessment of Prolanis using the theoretical framework of acceptability. This research is quantitative research with a descriptive approach. 180 respondents were selected using purposive sampling technique. Data analysis uses computerized descriptive statistical analysis. The research results showed that only 50.6% of respondents received Prolanis. The variable with the highest frequency is cost (97.8%). Meanwhile, the variable with the lowest frequency is burden (51.7%). As a recommendation, it is suggested to the government and BPJS Health to increase public understanding of the importance of using Prolanis in an effort to reduce the number of chronic diseases in Jambi City